2006
DOI: 10.1016/j.jcrs.2006.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intraocular lens surface properties with atomic force microscopy

Abstract: Atomic force microscopy was effective and accurate in analyzing IOL optics. The surface topography of IOLs may vary with different manufacturing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
7

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
2
32
0
7
Order By: Relevance
“…Hypothetically, an ideal biocompatible IOL material [16][17][18][19] should prevent the migration and proliferation of LECs, and, in combination with IOL edge design, may reduce the incidence of PCO. 5 The biocompatibility of IOLs in terms of the inflammatory response and LEC reaction has been evaluated in many studies. 6,16,17,20 The degrees of cell adhesion and migration vary depending on the IOL's material properties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypothetically, an ideal biocompatible IOL material [16][17][18][19] should prevent the migration and proliferation of LECs, and, in combination with IOL edge design, may reduce the incidence of PCO. 5 The biocompatibility of IOLs in terms of the inflammatory response and LEC reaction has been evaluated in many studies. 6,16,17,20 The degrees of cell adhesion and migration vary depending on the IOL's material properties.…”
Section: Discussionmentioning
confidence: 99%
“…This technology combines the capabilities of traditional ultramicroscopy with the ability to nondestructively analyze surface properties with nanometer resolution. 5,24,25 Advantages of AFM are the acquisition of 3-D images of the surface topography of solid interfaces, direct quantitative height information from the images obtained, and analysis of samples under near-use conditions. 5,13,25,26 Lombardo et al 5 found statistically significant differences in the surface roughness between various IOL materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations